SEROLOGICAL EVIDENCE OF SWINE LEPTOSPIROSIS IN AN ORGANISED FARM - Balakrishna, G; Ravi, G; Meenambagai, TV (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was undertaken to assess the prevalence of anti-leptospiral antibodies in swine reared in an organized farm located in the outskirts of Chennai city. Out of 63 samples collected, 57 ( 90.47 per cent) samples were found positive by Microscopic agglutination test with the prevalence of Australis (74.60 per cent), followed by Hardjo (30.16 per cent), Pomona (25.40 per cent), Autumnalis (23.81 per cent), Pyrogenes (17.46 per cent), Hebdomadis (6.35 per cent), Icterohaemorrhagiae (4.76 per cent), Canicola (3.17 per cent), Grippotyphosa (3.17 per cent), Javanica (3.17 per cent) and Tarassovi (3.17 per cent). The presence of antibodies indicated the circulation of leptospires among pigs. Hence this study alerts for the implementation of adequate sanitary measures on the farm to prevent the transmission of the infection to human in contacts.